Ecological and historical perspectives of rice cultivation in Kerala: a synthesis - Kumar, B Mohan; Kunhamu, TK (ORYZA-An International Journal of Rice, 2021)
Rice, the staple food for the people of Kerala, is cultivated since time immemorial in the state. The 15th centuryÂ Malayalam book of verse titled Krishi Gita describes the cultivation systems and locally adapted varieties of rice for various ecological and geographic regions of medieval Kerala. Although rice constitutes the principalÂ crop of the state, its area has been declining since the mid-1970s: i.e., from 8.82 lakh hectares in 1974-75, theÂ area has dropped to 2.02 lakh hectares in 2018-19 (77.1% reduction). The production has also declined fromÂ 13.76 lakh tonnes in 1972-73 to 5.78 lakh tonnes in 2018-19. While low per capita land availability (0.13 ha)Â has led to increasing land use intensification in Kerala, abandoned farmlands are also increasing, which is paradoxical. Conversion of paddy fields to cash crops is widespread. The net result is a major decline in areaÂ and production of rice in Kerala, which has made serious inroads into the state’s food production capacity. InÂ addition, it affected the diverse kinds of ecosystem services provided by the crop. Rice ecology in the state isÂ varied and is strongly conditioned by local climate and land forms. It rangesfrom below sea-level cultivationÂ (e.g., Kuttanad, Pokkali and Kole lands) to rice paddies in the High Ranges of Idukki and Wayanad (800-1500Â m above sea-level). Rice cultivation also has profound environmental implications including climate changeÂ impacts. This paper reviews the literature on ecological and historical aspects of rice production in Kerala.